Aportrait of the al-Gazera al-Foratuh and Bilad al-Sham in the fifth ALhagrah century/ The eleventh century AD, as Nasirkhusraw introduced it in his journey. - Muray , Sami (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The search treatsAportrait of the al-Gazera al-Foratuh and Bilad al-Sham in the fifth ALhagrah century/ The eleventh century AD, as Nasirkhusraw introduced it in his journey (book of travels) "Safar- nama". He explains his travelling line that tour between that Countries and he was revealing the position of life through his passing in those cities and Countries. He introduced important, various and documentary information in different sides. There was record for some historical news, he appeared the political situation there and for some civilized works for the being rulers in some areas. He showed much of the civilized sides, which gave light to the many numbers of the populated positions as the positions of the cities, their doors, towards, markets and their different, military, civilized, religion building and the carvings of that building and their mosaic. As they explain the sources of waters in each area whereas of rivers or of springs or the wells or of rain waters and the others. As the framings of trees and plants, occupations and hobbies, and the important commercial centers, coins and the libras, and some materials for trading in them. As they contain some social information, and some population in some cities and the religion in those areas, avisit to the holy places, some being habits and beliefs there and another thing.